Context-dependency of Purchasing and Supply Management: An empirical Institutional Theory Approach - Kerkfeld, Dieter; Hartmann, Evi (70th Annual Meeting of the Academy of Management - Dare to Care: Passion and Compassion in Management Practice and Research, AOM 2010, 2010)
Within the operations management literature a strong body of knowledge exists about the contribution of purchasing and supply management (PSM) to performance but little attention has been given to the potential influence of contextual factors on purchasing maturity and its relationship on performance. This study is rooted in institutional theory to formulate a number of propositions about contextual factors. First, we develop and empirically test a structural equation modeling (SEM) model of the influence of purchasing maturity to both operational performances and to business profitability. Purchasing maturity comprises four strategic PSM practices, supplier management, performance management, talent management, and cross-functional integration. The operational performances measure PSM's contribution to cost reductions, quality improvements, and innovation. Second, we analyze the influence of three contextual factors industry sector, degree of centralization, and reporting level of the chief purchasing officer (CPO) on the implemented level of purchasing maturity and its relationship on performance. This study combines multiple data sources, from telephone interviews, questionnaires, and objective financial data collected from a global, cross-industry sample of 306 major companies. Our results confirm that a sophisticated purchasing maturity has a positive impact on operational performance as well as an indirect positive effect on business profitability. Furthermore, the results indicate that both the implementation of purchasing maturity and its relationship on performance are to some degree context-dependent. This study provides CPOs with insights on how to improve and audit PSM's contribution towards performance, which is increasingly important during the current economic crisis.
WiSo-Import:2015-04-17:1276
Keywords: Innovation